Reactivation of Recall-Induced Neurons in the Infralimbic Cortex and the Basolateral Amygdala After Remote Fear Memory Attenuation - Khalaf, Ossama; Gräff, Johannes (Frontiers in Molecular Neuroscience, 2019)
Whether the attenuation of traumatic memories is mediated through the suppression of the original memory trace of fear by a new memory trace of safety, or through an updating of the original fear trace towards safety has been a long-standing question at the interface of neuroscience and psychology. This matter is of particular importance for remote fear memories as they lie at the core of stress- and anxiety-related disorders. Recently, we have shown that in the dentate gyrus, the effective attenuation of remote fear memories is accompanied by a reactivation of memory recall-induced neurons, and that the continuous activity of these neurons is critical for fear reduction. However, whether this also applies to other brain areas implicated in the storage of remote fear memories remains to be determined. Here, we show – by cellular compartment analysis of temporal activity using fluorescence in situ hybridization – that such reactivation also occurs in the basolateral amygdala and the infralimbic cortex, two brain areas known to be involved in fear memory attenuation. These results provide further experimental support for effective traumatic memory attenuation likely being mediated by an updating of the original fear trace towards safety.